Tomato class II glutaredoxin mutants generated via multiplex CRISPR/Cas9 genome editing technology are susceptible to multiple abiotic stresses - Kakeshpour, Tayebeh (Kansas State University, 2020)
Gene silencing technologies such as clustered regulatory short palindromic repeats (CRISPR)/Cas9 and RNA interference (RNAi) created a revolution in genome engineering. They are highly site-specific, simple, fast, and cost-effective. Since their discovery, gene silencing technologies have extensively been implemented in various organisms including humans, animals, plants, and microbes. They have been used for both basic science studies such as gene functional analysis and applied science such as medicine and crop improvement. In this work, we used multiplex CRISPR/Cas9 system to knock out all four members of the class II glutaredoxin (GRX) gene family including S14, S15, S16 and S17 in tomato and RNAi technology to express mouse complement 3 (C3) and complement factor 7 (CF7) small interfering RNAs (siRNAs) in lettuce. Reactive oxygen species (ROS) are induced under abiotic and biotic stresses and also as byproducts of aerobic metabolism, and their overproduction causes oxidative damage to macromolecules such as proteins, lipids, carbohydrates, and nucleic acids. GRXs are small ubiquitous proteins that are known to be involved in cellular redox homeostasis by reducing disulfate bonds and scavenging ROS. To investigate the functions of each member of class II GRX gene family in tomato’s response to abiotic stresses, single and multiple knockout lines for class II GRXs were obtained using multiplex CRISPR/Cas9 system. Mutant lines and wild-type plants were subjected to heat, drought, chilling, cadmium (Cd) toxicity, and short photoperiod stresses. Phenotyping data showed that members of the class II GRX gene family are critical for tomato’s growth, development, and survival under several abiotic stresses. Our findings propose novel functions for members of class II SlGRXs. RNAi technology can be utilized to target disease-related proteins. However, the application of siRNAs is challenging predominantly due to the difficult delivery and instability of siRNA into the host system. Recent findings of bioactivity and bioavailability of plants’ miRNAs through animals’ digestive systems led to the newly introduced field of dietary siRNAs. Animal’s siRNA can be expressed in plant tissues and delivered as dietary siRNA. Here, an expression vector made based on a rice miRNA backbone, Osa-MIR528, was utilized to construct two plant expression vectors containing siRNAs silencing mouse C3 and CF7 proteins. Both C3 and CF7 proteins are involved in blood clotting which could lead to cardiovascular dysfunction. Expression of both primary and mature C3 and CF7 siRNAs in lettuce was validated by semi quantitative real-time PCR and end-point PCR, respectively, and was confirmed via Sanger sequencing. Established amiRNA system in lettuce through this work will have further applications. As an edible leafy plant with high biomass, lettuce can be used as a valuable host to produce various diseases targeting siRNAs.
Keywords: Abiotic Stress; CRISPR/Cas9; Glutaredoxin; Tomato